Relationship Bonds and Service Provider’s Emotional Labor: Moderating Effects of Collectivism - Lee, Myoung-Soung; Han, Sang-Lin; Hong, Suji; Hyun, Hyowon (Frontiers in Psychology, 2019)
Since service providers directly conduct emotional labor to customers, it is important to identify the factors influencing emotional labor of service providers. Even though the studies identifying the predisposing factors influencing emotional labor are taking place, there is no empirical evidence confirming how relationship bonds, which have been established between corporations and service providers, are related to emotional labor. This study examined the influences of relationship bonds on emotional labor through person-organization fit (P-O fit) and the moderating effects of collectivism between P-O fit and emotional labor. Analysis was conducted by performing questionnaire surveys targeting 365 employees in the financial industry. As a result of the analysis, it has been found that financial bonds, social bonds, and structural bonds enhanced P-O fit and P-O fit improved deep acting. In addition, this study identified that collectivism of service providers strengthened the influence of P-O fit toward deep acting. This study not only suggested the empirical evidence identifying the process of relationship bonds influencing emotional labor but also expanded the scope of study by examining moderating roles of collectivism in cultural psychology aspect.